An Analytical Study of Marketing Mix of Selected Brands of Vegetable Oil in Northern India - Agarwal, Brijesh Kumar; Bansal, Anamica (Journal of Commerce and Trade, 2018)
Edible oil industry happens to be the key player in the economic development of the country. It is a sector that provides revenue not only through industry but also through the agricultural sector. The country is becoming more self depend in the production and consumption of edible oils. Innovative and scientific method of oil production is one of the basic aspects of oil industry. The continuous process of oil manufacturing through research and development making industry more viable the industries are using upgraded technology for making oils. The government is also taking good number of steps for better promotion of domestic oil industry. India is country where 25% of the population is suffering from cholesterol and heart related diseases. Maximum number of deaths is due to heart congestion and heart related attacks, which is duly recognized by oil industry by providing double and triple refined oil to protect the human heart. However there is a need for the government to take necessary steps to punish culprits of duplicate oil business. This will enhance the confidence of the people and the government to further boost the oil industry.